PENGARUH MEDIA SOSIAL SEBAGAI PLATFORM BISNIS DIGITAL TERHADAPMINAT BERWIRAUSAHA - Alfiah Natasya, Firda; Zakaria Al Anshori, Asep; Aziz, Abdul (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study aims to determine whether there is an effect of social media as a digital business platform on entrepreneurial interest in IUQI students. This study uses quantitative methods, the sample in this study were students of Institut Ummul Quro Al-Islami Bogor totaling 94 respondents, data collection instruments in the form of questionnaires, observations, and interviews using a Likert scale. Data analysis techniques in this study used validity tests, reliability tests, Chi-Square tests. Based on the result of the study, it shows that the p-value of pearson chi-square 552.626 > t-tabel value 1.66123, rejecting Ho and accepting Ha. So, student interest in entrepreneurship is significantly influenced by social media variables. It can be concluded that the higher the utilization of social media in students, the higher the interest in entrepreneurship